Recovering Lost Light: Discovery of Supernova Remnants with Integral Field Spectroscopy - Galbany, Lluís (Institute of Physics Publishing, 2025)
We present results from a systematic search for broad (≥ 400 km s−1) Hα emission in integral field spectroscopy data cubes of ∼1200 nearby galaxies obtained with PMAS and MUSE. We found 19 unique regions that pass our quality cuts, four of which match the locations of previously discovered supernovae (SNe): one Type IIP and three Type IIn, including the well-known SN 2005ip. We suggest that these objects are young Supernova remnants (SNRs), with bright and broad Hα emission powered by the interaction between the SN ejecta and dense circumstellar material. The stellar ages measured at the locations of these SNR candidates are systematically lower by about 0.5 dex than those measured at the locations of core-collapse (CC) SNe, implying that their progenitors might be shorter lived and therefore more massive than a typical CCSN progenitor. The methods laid out in this work open a new window into the study of nearby SNe with integral field spectroscopy.